Respostas

2013-10-04T14:50:18-03:00
M(xM,yM)

xM =  \frac{(xA + xB)}{2}  =  \frac{(0+4)}{2} = 2
yM = \frac{ (yA + yB)}{2}  =  \frac{(4+0)}{2}  = 2

M(2,2)

 dOM =  \sqrt{((xM-xO)^2+(yM-yO)^2)}  =  \sqrt{((2-0)^2+(2-0)^2)}  = \sqrt{(4+4)}  =  \sqrt{8} = 2 \sqrt{2}

P(xP,yP)

xP =  \frac{(xO + xM)}{2} =  \frac{(0 + 2)}{2}  = 1
yP =  \frac{(yO + yM)}{2} =  \frac{(0+2)}{2} = 1

P(1,1)

 R = \frac{dOM}{2}  = \sqrt{2}

(x-xP)^2+(y-yP)^2=R^2
(x-1)^2 + (y-1)^2 =( \sqrt{2})^2

(x-1)^2 + (y-1)^2 = 2
16 3 16
Não tá aparecendo ali, mas depois de Raiz de (2-0)² + (2-0)² = Raiz de 4+4